Pengaruh Inflasi, Suku Bunga, dan Jumlah Uang Beredar terhadap Nilai Tukar - Noor, Zulki Zulkifli (Jurnal Trikonomika, 2011)
The general objective of this study was to know how far the effect to changing of Rupiahâs Exchange Rate to American Dollar by three factor of economic: inflation rate, interest rate and money supply, and also to know its causality link. The evaluations are carried out by several data of inflation rate, interest rate and money supply from that two country. A multiple regression was done to determine how far the effect of the variables above. Some statistical test, that is related to regression, was done too. Also Grangerâs causality test was done to know the causality link. Based upon data analyzed in this study, there are some conclusions as follow: (1) if inflation rate, interest rate and money supply is used partially, there is no significant influence or effect on changing of exchange rate. (2) in other way, if those factor is integrated in using of analysis, there is quite significant. (3) and the last, for interest rate and money supply have causality relation to changing of exchange rate, but not inflation rate.